Continuity in general practice as predictor of mortality, acute hospitalisation, and use of out-of-hours care: a registry-based observational study in Norway - Sandvik, Hogne; Hetlevik, Øystein; Blinkenberg, Jesper; Hunskaar, Steinar (British journal of general practice, 2022)
Continuity, usually considered a quality aspect of primary care, is under pressure in Norway, and elsewhere. To analyse the association between longitudinal continuity with a named regular general practitioner (RGP) and use of out-of-hours (OOH) services, acute hospital admission, and mortality. Registry-based observational study in Norway covering 4 552 978 Norwegians listed with their RGPs. Duration of RGP-patient relationship was used as explanatory variable for the use of OOH services, acute hospital admission, and mortality in 2018. Several patient-related and RGP-related covariates were included in the analyses by individual linking to high-quality national registries. Duration of RGP-patient relationship was categorised as 1, 2-3, 4-5, 6-10, 11-15, or >15 years. Results are given as adjusted odds ratio (OR) with 95% confidence intervals (CI) resulting from multilevel logistic regression analyses. Compared with a 1-year RGP-patient relationship, the OR for use of OOH services decreased gradually from 0.87 (95% CI = 0.86 to 0.88) after 2-3 years' duration to 0.70 (95% CI = 0.69 to 0.71) after >15 years. OR for acute hospital admission decreased gradually from 0.88 (95% CI = 0.86 to 0.90) after 2-3 years' duration to 0.72 (95% CI = 0.70 to 0.73) after >15 years. OR for dying decreased gradually from 0.92 (95% CI = 0.86 to 0.98) after 2-3 years' duration, to 0.75 (95% CI = 0.70 to 0.80) after an RGP-patient relationship of >15 years. Length of RGP-patient relationship is significantly associated with lower use of OOH services, fewer acute hospital admissions, and lower mortality. The presence of a dose-response relationship between continuity and these outcomes indicates that the associations are causal.